EFEKTIFITAS KOMUNIKASI KONSELING TERHADAP ORANG DENGAN HIV/AIDS (ODHA) DALAM MEMPERPANJANG HARAPAN HIDUP (Studi Kasus Konselor Di Komite AIDS HKBP) - Ardi Tambunan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2020)
The purpose of this study was to analyze the communication process, communication barriers and effective communication on HIV / AIDS counseling in the HKBP AIDS Committee. The theory used is Communication theory, Communication Process Model Shannon and Weaver, Interpersonal Communication Theory, Johari Window Theory This research uses qualitative descriptive method and case study. The data was collected for three months through observation and in-depth interviews of two counselors, two people living with HIV and one community leader. Data analysis using interactive model The important finding of this research is the communication process in HIV / AIDS counseling is the process of delivering HIV / AIDS information by counselor to ODHA client whose purpose is to provide support and strengthening. The form of communication in HIV/AIDS counseling is interpersonal communication.